Beyond Storage: Evaluating the Utilization of Learning Management Systems in Higher Education - Mutanga, Murimo Bethel; Mhlongo, Vincent Xolani; Pillay, Fiona (IJIE (Indonesian Journal of Informatics Education), 2023)
In the rapidly evolving landscape of higher education, the integration of Learning Management Systems (LMSs) has become pivotal, transcending mere content uploading to necessitate a deeper fusion of technology, pedagogy, and content knowledge, as emphasised by the Technological Pedagogical Content Knowledge (TPACK) model. This study addresses the knowledge gap in assessing the alignment of the usage LMSs with the TPACK framework through a mixed-method approach. Analysing LMS usage patterns and distributing questionnaires to academics reveals the predominant use of LMSs for basic content storage, with limited incorporation of multimedia resources and infrequent utilisation of external and analytical tools. These findings raise concerns about universities' optimal utilisation of technology investments, highlighting the need to reassess LMS value and potential redesign. The study underscores the importance of enhanced training and support for academics to align LMSs with TPACK principles, emphasising the necessity of understanding this relationship. By doing so, educators can employ transformative strategies that extend beyond conventional boundaries, offering a more enriched educational experience.